3(6x+8)=9x-16-x

Simple and best practice solution for 3(6x+8)=9x-16-x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(6x+8)=9x-16-x equation:


Simplifying
3(6x + 8) = 9x + -16 + -1x

Reorder the terms:
3(8 + 6x) = 9x + -16 + -1x
(8 * 3 + 6x * 3) = 9x + -16 + -1x
(24 + 18x) = 9x + -16 + -1x

Reorder the terms:
24 + 18x = -16 + 9x + -1x

Combine like terms: 9x + -1x = 8x
24 + 18x = -16 + 8x

Solving
24 + 18x = -16 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
24 + 18x + -8x = -16 + 8x + -8x

Combine like terms: 18x + -8x = 10x
24 + 10x = -16 + 8x + -8x

Combine like terms: 8x + -8x = 0
24 + 10x = -16 + 0
24 + 10x = -16

Add '-24' to each side of the equation.
24 + -24 + 10x = -16 + -24

Combine like terms: 24 + -24 = 0
0 + 10x = -16 + -24
10x = -16 + -24

Combine like terms: -16 + -24 = -40
10x = -40

Divide each side by '10'.
x = -4

Simplifying
x = -4

See similar equations:

| -8x-3=-48 | | 5x+2y=12findy | | y=x^2-2x-6y=4x+10 | | -16x^2+128x+2=0 | | (3x+2x+2+2x+2+5x+3)5= | | (-2x+3)(-x+15)=15 | | 2(x-6)=9-5x | | 6w-10w^3= | | (-2x)+(-x-16)=0 | | log(a)4=2 | | 3(x-2)=2x+2(x-8) | | 25(4-2x)=5(-6x) | | (5x-2)=(9x) | | -3(m+2)+6m=9(m+-1) | | 9a+33ab+-76b+65c+17a+51ab+-80b+13c= | | 3+16x+12=11x+15+5x | | -2c+3.7=-0.5 | | 21ab+-50b+13c+17a+30ab+-30b= | | 6x-42=9x | | 12x+2=12x-5 | | 9a+12ab+-26b+52c+21ab+-50b+13c= | | 7*4x=x+8 | | 8x-72=5x+25 | | 15ab+-24b+17a+15ab+-6b= | | 7x+14x+21x+28x=360 | | 94+84+62+y=(4-2)180 | | 94+84+72+y=(4-2)180 | | -2(1+7x)= | | 3c*5a*2a+8= | | 6ab+-26b+13c+15ab+-24b= | | 15a+25b= | | 101+80+65+y=(4-2)180 |

Equations solver categories